2018
DOI: 10.1002/joa3.12042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new KCNQ1 frameshift mutation associated with Jervell and Lange‐Nielsen syndrome in 2 Iranian families

Abstract: Jervell‐Lange Nielsen syndrome (JLNS) with autosomal recessive inheritance is a congenital cardiovascular disorder characterized by prolongation of QT interval on the ECG and deafness. We have performed molecular investigation by haplotype analysis and DNA Sanger sequencing in 2 unrelated Iranian families with a history of syncope. Mutational screening of KCNQ1 gene revealed the novel homozygous frameshift mutation c.733‐734delGG (p.G245Rfs*39) in 2 obviously unrelated cases of JLNS which is probably a founder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Examination of the parents of two patients showed heterozygosity for this mutation. In our previous study[15], using STR markers, we demonstrated this frameshift mutation in two obviously unrelated families with the same origin, which may represent a founding effect.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Examination of the parents of two patients showed heterozygosity for this mutation. In our previous study[15], using STR markers, we demonstrated this frameshift mutation in two obviously unrelated families with the same origin, which may represent a founding effect.…”
Section: Resultsmentioning
confidence: 84%
“…The sequence analysis of the index patient demonstrated the absence of mutation in the SCN5A and KCNH2 genes but showed a novel homozygous mutation, c.1426_1429delATGC (M476Pfs*4), in KCNQ1 gene. Five patients screened previously were found to have a missense mutation in two RWS families[16] and two frameshift mutations in three JLNS families[17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a homozygous frameshift mutation in USH2A, c.236_239dup p.(Gln81Tyrfs*28), proband 58 presented with a medically actionable pathogenic variant, c.733_734del p.(Gly245Argfs*39) in KCNQ1 (Table 1) (Amirian et al 2018), which is associated with long QT syndrome 1 (OMIM 192500) and familial atrial fibrillation 3 (OMIM 607554).…”
Section: Usher Syndrome As the Most Common Cause Of Dual Sensory Lossmentioning
confidence: 99%